Intervention Implementation of Tools of the Mind for Preschool Children’s Executive Functioning - Goble, Priscilla; Flynn, Toria; Nauman, Cambrian; Almendarez, Pond; Linstrom, Meagan (Frontiers in Psychology, 2021)
One of the more prominent early childhood interventions focused on the development of executive function (EF) skills is Tools of the Mind (Tools; Bodrova & Leong, 2019). Intervention studies comparing Tools classrooms with control classrooms, however, reveal inconsistent findings for children’s EF outcomes. The current study utilizes Head Start CARES teachers assigned to the Tools of the Mind enhancement intervention (Tools; N = 75) and the children in their classrooms (N = 738). Relations between teachers’ characteristics (i.e., teaching experience, psychological well-being, and educational background), training dosage and implementation (i.e., training attendance, coach rated fidelity, and observed scaffolding), and the interaction among these factors were examined as predictors of classroom-level gains in EF. Results revealed several significant moderation effects indicating that Tools implementation is related to classroom EF gains for some but not all teachers.